Recent Progress in Coordination Chemistry - Segľa, Peter; Pavlik, Ján (MDPI - Multidisciplinary Digital Publishing Institute, 2023)
The following reprint is based on the discussions initiated at the 28th International Conference on Coordination and Bioinorganic Chemistry (ICCBIC), which was held between 5 and 10 June 2022 at Smolenice Castle, Slovakia. As is apparent, this year's ICCBIC established a partnership with the MDPI publishing house. Therefore, we invite you to form a picture of the spirit of the conference by reading this reprint version of Special Issue of Inorganics, which is devoted to this conference. In total, ten contributions were submitted, of which eight are original papers and two are perspectives.